2015
DOI: 10.1089/end.2015.0255
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormone Levels May Not Explain Gender Differences in Development of Nephrolithiasis

Abstract: We found no significant association of sex steroid hormone levels with the risk of nephrolithiasis formation in men, although a weak trend toward an increased risk with elevated testosterone was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The same result was also observed in our cohort study. However, the exact pathophysiology of gender difference in urolithiasis remains uncertain [ 19 ]. Some studies stressed on the protective effect of estrogen, while others concluded testosterone as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The same result was also observed in our cohort study. However, the exact pathophysiology of gender difference in urolithiasis remains uncertain [ 19 ]. Some studies stressed on the protective effect of estrogen, while others concluded testosterone as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all this evidence, the relationship between testosterone levels and nephrolithiasis is still in the aura of uncertainty and is a subject of ongoing research. While some studies have reported an association between elevated testosterone levels and an increased risk of kidney stones, other studies have not found any correlation [11,12,24,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 93%
“…Clouding the discussion further, one study reported an increased risk of stones with lower testosterone levels [20]. A single study found no association with testosterone [21]. Our endocrinologists only evaluate free testosterone due to previous evidence that it is more sensitive than total testosterone for the diagnosis of hyperandrogenic disorders such as PCOS [22].…”
Section: Discussionmentioning
confidence: 99%